Synthesis and Properties of Platinum Nanoparticles by Pulsed Laser Ablation in Liquid - Mendivil Palma, María Isabel; Krishnan, Bindu; Rodriguez, Guadalupe Alan Castillo; Das Roy, Tushar Kanty; Avellaneda Avellaneda, David; Shaji, Sadasivan (2016)
Platinum (Pt) nanoparticles were synthesized by pulsed laser ablation in liquid (PLAL) technique in different liquids (acetone, ethanol, and methanol). Ablation was performed using a Q-switched Nd:YAG laser with output energy of 230 mJ/pulse for 532 nm wavelength. Ablation time and laser energy fluence were varied for all the liquids. Effects of laser energy fluence, ablation time, and nature of the liquid were reported. The mean size, size distributions, shape, elemental composition, and optical properties of Pt nanoparticles synthesized by PLAL were examined by transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), and UV-Visible absorption spectroscopy.